MARKETING MANAGEMENT EDUCATION (Case Study in SD Kemala Bhayangkari 02 Semarang) - Musino, Musino; Raharjo, Tri Joko; Soesilowati, Etty (Educational Management, 2018)
This study discusses the educational marketing activities conducted by SD Kemala Bhayangkari 02 Semarang. Geographically SD Kemala Bhayangkari 02 Semarang is located in the city center. Despite its location in the middle of the city but the number of students every year continues to decline. This is evidenced by the data on the number of students over the last five years indicates that there is a Decrease in students every year. This study aims to analyze: 1) marketing management services elementary education Kemala Bhayangkari 02 Semarang. 2) supporting and inhibiting factors of education services marketing. The method used qualitative research method. The results Showed. 1) The concept of education marketing management conducted by SD Kemala Bhayangkari 02 Semarang in the form of analysis, planning, implementation and supervision. 2) Inhibiting factors in the marketing of education services include the lack of excellent programs that characterize children after graduating from the school, as well as intense competition in attracting students with other public and private schools. The supporting factor is the SD Kemala Bhayangkari shaded by Police CENTRAL. Conclusion in this research is Implementation of concept and function of marketing management done roomates still not optimal. It is advisable to all the board of the foundation, committee, and all teachers and employees of SD Kemala Bhayangkari 02 Semarang to Make optimum quality improvement to face the competition the which is very open in this era.